Analisis Pemetaan Bisnis Badan Usaha Milik Kampung Agro Makmur Kampung Depokrejo Kecamatan Trimurjo Kabupaten Lampung Tengah - Bambang Suhada; Sri Retnaning Rahayu; Agus Setiawan (Jurnal Manajemen DIVERSIFIKASI, 2025)
The strategy of strengthening the village economy through BUMDes is one of the solutions torelease the dependence of village communities on government assistance and to exploreregional potential. The object of this research is business mapping using Business ModelCanvasing. This research activity was conducted at the Village-Owned Enterprises inDepokrejo Village, Trimurjo District, Central Lampung Regency. The research populationwas the Village Officials and the management of the Village-Owned Enterprises. Datacollection techniques using interviews and documentation and literature studies. Theanalytical tool used is using Business Model Canvas analysis. The results showed that theCustomer Segment of BUMKam Agro Makmur Kampung Depokrejo is a company thatrecycles waste and people who need recycled products for the purposes of creative industrieson a small scale. The portion of the value of the products produced has been sorted from the household so that not only the waste produced has been properly sorted. Business networkwith factories within Lampung province and also between provinces. The main source ofincome is the difference between the purchase price and the selling price of the number ofproducts produced.Key Resources consist of people who deposit recyclable waste, businessentity management and facilities and infrastructure. Key Activities provide recyclable wastethat has been grouped into various types such as plastic waste, paper, cardboard, iron andothers Key partnerships with the community, product collection factories and villageapparatus institutions Cost structure includes capital costs, operational costs, overhead costsand costs for salaries of administrators